What Are the Costs of Diagnostics and Treatment of Lyme Borreliosis in Poland? - Rogalska, Anna Maria; Pawełczyk, Olga; Solarz, Krzysztof; Holecki, Tomasz (Frontiers in Public Health, 2021)
Introduction: Lyme borreliosis (LB) is a growing epidemiological threat to many areas of the world, including North America and Europe. Due to lack of effective protection against this disease, it seems important to make a quick diagnosis to effectively treat and prevent its serious consequences. Objectives: The aim of the study was to assess the costs of diagnosis and treatment of Lyme disease in Poland. Material and methods: The costs related to the diagnosis and treatment of Lyme disease from the medical payers side were analyzed. Results: The costs of hospitalization due to LB per 1 patient from 2014 to 2017 did not decrease below 530 Euro, and in 2018 amounted to 582.39 Euro, which constituted 53.10% of the average monthly salary this year. Conclusions: In the analyzed period (2008-2018) the number of people covered by medical services due to Lyme disease increased, both in hospitalization and outpatient specialist care. Although the costs of hospitalization are the highest, we can notice a decrease in the percentage share of costs of hospitalization for outpatient specialist care.